2011
DOI: 10.1002/bmc.1627
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of thiram in water, soil and plants: a study by high‐performance liquid chromatography

Abstract: A comprehensive study was conducted to evaluate the persistence of thiram in water and soil under controlled conditions and on two plants, namely tomato and radish, in field conditions. In order to follow the decay of the pesticide, an HPLC procedure was developed employing an octadecyl endcapped RP-C18 column using a mixture of acetonitrile and water as the mobile phase and an ultraviolet detector. Studies conducted in water at different temperature, pH and organic content revealed that the persistence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…When compared with those different traditional complicated and timeconsuming methods such as chromatography, UV-Vis spectrophotometry, enzyme-linked immunosorbent assay and chemiluminescence analysis (Gupta et al 2012;Rastegarzadeh et al 2013;Queffelec et al 2001;Waseem et al 2010), the analytical method based on SERS technique is promising as it can be used for rapid detection of trace thiram. Figure 7 shows the Raman spectra of thiram in ethanol with concentrations decreasing from 1 9 10 -3 to 1 9 10 -7 M using the FSA composites as SERS substrate.…”
Section: Sers Detection Of Thirammentioning
confidence: 99%
“…When compared with those different traditional complicated and timeconsuming methods such as chromatography, UV-Vis spectrophotometry, enzyme-linked immunosorbent assay and chemiluminescence analysis (Gupta et al 2012;Rastegarzadeh et al 2013;Queffelec et al 2001;Waseem et al 2010), the analytical method based on SERS technique is promising as it can be used for rapid detection of trace thiram. Figure 7 shows the Raman spectra of thiram in ethanol with concentrations decreasing from 1 9 10 -3 to 1 9 10 -7 M using the FSA composites as SERS substrate.…”
Section: Sers Detection Of Thirammentioning
confidence: 99%
“…Several procedures for the extraction of the pesticide from water were tried and ethyl acetate was found as the most suitable extractant for water with the recoveries of 90 ± 5%. [12] In brief, the spiked water sample (4 mL) was extracted with ethyl acetate (4 mL×2). The ethylacetate layer was separated and dried over anhydrous Na 2 SO 4 and concentrated using a rotary evaporatar for further analysis.…”
Section: Degradation Studiesmentioning
confidence: 99%
“…It was found that temperature, pH and field conditions play an important role in the decomposition of thiram . [12] In view of this a composite systematic study has been carried out on the degradation of thiram in soil (pH 5.1 and 8.1), water (pH 5.5 and 8) at constant temperature 28 ± 2 • C and on/in plants. Based on the identification of byproducts metabolic pathways have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum and minimum air temperatures recorded were 28.4 and 25.9 °C, respectively, and the mean humidity level was 80%. It was reported that the dissipation of thiram depended on the nature of the medium and environmental conditions such as temperature and pH (Gupta et al, 2012b).…”
Section: Dissipation Kinetics Of Thirammentioning
confidence: 99%
“…One previous study on the thiram degradation was carried out under controlled laboratory conditions (Gupta et al, 2012b). Very recently, Liu et al (2015) reported thiram dissipation and residual levels for potato cultivation in the open field.…”
Section: Introductionmentioning
confidence: 99%